Designing an Electronic Bag Based on the Model (70: 20: 10) and its Effectiveness on Developing the Skills of Producing Data Tables for Female Students in the Department of Biology - Ghanim Alsumaidaee, Ahmed Luay (Journal of Tikrit University for Humanities, 2023)
The aim of the research is to design an electronic educational bag based on a model (70: 20: 10) and to demonstrate its effectiveness in developing the skills of producing data tables among female students of the Department of Biology. The researcher followed the experimental approach with the design of one experimental group with pre and post measurement, The research group consisted of (62) third- stage female students in the Department of Biology at the College of Education for Girls, University of Mosul. The researcher designed an electronic bag based on the model (70: 20: 10) according to the stages of educational design "SAM", The study tools consisted of an achievement test for the skills of producing data tables and a practical test for the same skills, and the data were treated statistically using the coefficient of difference, Pearson’s correlation coefficient, Cronbach’s alpha coefficient, the Paired Samples T-test, the equation for calculating the effect size of the Eta square, and the Black equation. The results concluded that there are statistically significant differences between the mean scores of the female students of the experimental group in the pre and post applications of the cognitive achievement test for the skills of producing data tables in favor of the post application. There are statistically significant differences between the mean scores of the female students of the experimental group in the pre and post applications to test the practical performance of the skills of producing data tables in favor of the post application. The results also revealed the effectiveness of the electronic bag based on the model (70: 20: 10) in developing the skills of producing data tables among female students of the Department of Biology. Based on the results of the research, a set of relevant recommendations and proposals was presented.